Influence of isomerism on recrystallization and cocrystallization induced by CO2 as an antisolvent12. Issue 29 (7th August 2015) - Harscoat-Schiavo, C.; Neurohr, C.; Lecomte, S.; Marchivie, M.; Subra-Paternault, P.
<x xml:space="preserve">Abstract</x> The position of the amine group in aminosalicylic acid has a significant impact not only on polymorph or cocrystal formation but also on the crystal shape during crystallization using CO2 as an antisolvent.